GREEN LIFESTYLE AND POS: WHICH ONE DOES HAVE THE BIGGEST ROLE IN INFLUENCING THE INFLUENCE OF GREEN HRM ON EMPLOYEE PERFORMANCE? - Nury Ariani Wulansari; Rini Setyo Witiastuti; Siti Ridloah (Jurnal Bisnis Manajemen, 2019)
This study aims to investigate the effect of Green HRM on performance, and how the correlation is moderated by Perceived Organizational Support (POS) and green lifestyle. The population of this study was employees in state universities in Central Java Province. The methods of data collection were by employing observation, interviews, and questionnaires. The sampling technique used purposive sampling technique, and the number of samples was 232. Structural Equation Modeling (SEM) analysis by using warp PLS program was used to test the hypothesis. The study result shows that Green HRM affects employee performance. Perceived organizational support strengthens the correlation of Green HRM and organizational identification. Meanwhile, green lifestyle does not become a moderating variable in the correlation of Green HRM and employee performance. This study provides a description of the importance of Green HRM to be applied in profit or non-profit organizations. This study provides a new pointof view that Green HRM has a vital role in the university context.